Bacterial zoonoses impacts to conservation of wildlife populations: a global synthesis - Hirst, Kristen M.; Halsey, Samniqueka J. (Frontiers in Conservation Science, 2023)
Emerging infectious diseases have significantly increased in recent years; approximately 60% of these emerging diseases are of zoonotic origin, and of those, around 70% were identified to start with wild animals. To better understand the impacts of zoonotic diseases on wildlife, there is a need to identify the distribution and impact of zoonotic pathogens in wildlife, particular those species with threatened populations. We constructed a zoonotic disease database identifying wildlife hosts for each bacterial zoonotic disease and recorded clinical signs of disease for each host-pathogen relationship if found. Species of least concern were found to have a significantly higher prevalence and richness of zoonotic bacterial diseases (n= 0.0608, x 2 =5.898, p=0.01516). The taxonomic level Order was found to be the best model predictor for pathogen richness, and the Artiodactyla and Carnivora contain a significantly higher pathogen richness than other Orders. Understanding the impacts and distribution of bacterial zoonoses in wildlife populations can help in planning for future wildlife management efforts, particularly in species of conservation concern and wildlife disease monitoring.Commented [HK1]: L12-13: "The taxonomic level Order was found to be the best model for pathogen richness". Please substitute "the best model" with "the best predictor" since it is not a model, it is an explanatory variable.